Open Personality – Isolated By Members of the Fifth Session of the Kurdistan-Iraqi Parliament - Hassan, Arslan A.; Aziz, Omar I. (Mitanni Journal of Humanitarian Sciences, 2023)
This study aims to explore the extraversion and introversion personality types among members of the fifth round of Kurdistan parliament - Iraq and according to demographic variable such as gender (Male & Female) and certificate level. The researcher used descriptive method. The population consisted of members of the fifth round of Kurdistan parliament – Iraq. The sample was (63) members of parliament which involved 46 male and 17 female according to certificate level ( high school, diploma, bachelor’s degree , Master, and Doctoral Degree) which they were selected randomly. (hssen, 2013) scale was used for measuring extraversion and introversion personality types which consisted of 18 items. for analyzing the data the researcher used (SPSS). For finding reliability (test- retest method) and (split- half method) were applied . Because the items of the scales were single the researcher used Spearman-Brown coefficient and the Gettman coefficient of split-half, the test- retest reliability value was (0.88), which is statistically significant at the level of (0.05) which is a strong correlation. The value of reliability with Gettman coefficient was (0.901)and with Spearman Brown was ( 0.94). Finally, the results indicated that the sample of the research is introversion personality type oriented , and there are no significant differences between extraversion and introversion personality according to gender variable, but there are significant differences between extraversion and introversion personality and certificate degree in favor of master degree, which means those who hold master degree are more likely to be extroverted person.